2015
DOI: 10.5455/medscience.2015.04.8250
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescribing Pattern in Dermatophytosis at the Medical Outpatient Clinic of a Tertiary Healthcare in Karnataka, India

Abstract: Aim of this study is to ascertain the drug prescribing pattern of the patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…This result slightly different from the study by Giri et al which showed majority of oral prescription of terbinafine but sertaconazole was most commonly prescribed topical antifungal. 17 This was also in accordance with study by Narang et al which also showed terbinafine and topical azoles as the most common drugs used in dermatophytosis. 18 In a study conducted by Kamerkar et al it was seen that 58.28 % of drugs were prescribed as oral formulation and 41.71% were prescribed as topical formulation which was slightly different from the result obtained in our study showing 49.42% oral and 50.57% as topical prescription.…”
Section: Discussionsupporting
confidence: 90%
“…This result slightly different from the study by Giri et al which showed majority of oral prescription of terbinafine but sertaconazole was most commonly prescribed topical antifungal. 17 This was also in accordance with study by Narang et al which also showed terbinafine and topical azoles as the most common drugs used in dermatophytosis. 18 In a study conducted by Kamerkar et al it was seen that 58.28 % of drugs were prescribed as oral formulation and 41.71% were prescribed as topical formulation which was slightly different from the result obtained in our study showing 49.42% oral and 50.57% as topical prescription.…”
Section: Discussionsupporting
confidence: 90%
“…Topical miconazole was the most commonly prescribed drug followed by sertaconazole and eberconazole. A similar study by Giri VP et al (2015) reported that terbinafine was the most commonly prescribed topical antifungal (22.79%), followed by sertaconazole (20.25 %) and ketoconazole (9.49 %) [15]. The use of topical azoles in our study is supported by previous studies that have reported a similar efficacy between topical allylamines and topical azoles [13].…”
Section: Discussionsupporting
confidence: 90%